(α, F)-Geraghty-type generalized F-contractions on non-Archimedean fuzzy metric-unlike spaces - Alam Khairul Habib; Rohen Yumnam; Tomar Anita (Demonstratio Mathematica, 2024)
In this study, we generalize fuzzy metric-like, non-Archimedean fuzzy metric-like, and all the variants of fuzzy metric spaces. We propose the idea of fuzzy metric-unlike and non-Archimedean fuzzy metric-unlike, respectively. We also propose the idea of (α,F)\left(α ,F)-Geraghty-type generalized FF-contraction mappings utilizing fuzzy metric-unlike and non-Archimedean fuzzy metric-unlike spaces. We investigate the presence of unique fixed points using the recently introduced contraction mappings. In order to complement our study, we consider an application to dynamic market equilibrium.